Community Response to Amorphophallus sp. Agroindustrial Empowerment Using Partial Least Square - Ahmad Syihab Fahmi Qowim Romadhon Mubarok; Imam Santoso (HABITAT, 2018)
Amorphophallus sp is one of the most important crops developed in Indonesia, both as food crops as well as industrial raw materials. This plant is widely developed in through various community empowerment programs such as farmer empowerment conducted by PERUM PERHUTANI Unit II of East Java in cultivated area of 1.605,3 Ha. This study focused to analyze the public response to Amorphophallus sp cultivation in empowering communities. The method used was quantitative approach and inferential statistics using Partial Least Square (PLS). The community, in the study area, already have the knowledge of Amorphophallus sp cultivation. The communities have experienced to implement postharvest practices such as chip. The community response on the implementation Amorphophallus sp cultivation has been good, and feel the benefits of cultivating mainly from the economic aspect. Due to economic factors, some people still sell the bulbs Amorphophallus sp without process into a more value-added products. PLS analysis showed that the variable of community attitude and participation significantly affected the benefits of cultivation in the community. The higher the participation, the better the achievement of community empowerment. However, the variable of cultivation information, the variable of the information of post-harvest handling, and the variable of supporting facilities did not significantly influence the community response. Furthermore, the variable of cultivation information, the variable of information of post-harvest handling, the variable of supporting facilities, the variable of society attitude did not significantly influence on the community participation.